2002
DOI: 10.1159/000048905
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Drug Reactions: Mechanisms and Assessment

Abstract: Adverse drug reactions (ADR) are an important clinical problem. They account for about 5% of all hospital admissions and cause death in approximately 0.01% of surgical patients. The mechanisms leading to ADR beyond IgE-mediated allergy are still poorly understood. The importance of chemically reactive drug metabolites and the involvement of T-lymphocytes in many drug hypersensitivity reactions have been highlighted in recent years. ADR are diagnosed on clinical grounds and the temporal relation between drug in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 32 publications
0
4
0
1
Order By: Relevance
“…3,4 On the other hand, HIT has features that are atypical for a TD immune disorder. Whereas TD drug reactions to drugs like penicillin or sulfonamides 5,6 are typically long-lived and associated with immunologic memory, antibodies to PF4/heparin appear to be transient 7 and recurrences do not invariably follow heparin reexposure, suggesting the absence of immunologic memory in HIT. 7,8 These observations, in addition to the extraordinary prevalence of PF4/heparin antibody formation in clinical settings such as cardiopulmonary bypass, 9 cast doubt on the requirement for T-cell help in the generation of anti-PF4/heparin antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 On the other hand, HIT has features that are atypical for a TD immune disorder. Whereas TD drug reactions to drugs like penicillin or sulfonamides 5,6 are typically long-lived and associated with immunologic memory, antibodies to PF4/heparin appear to be transient 7 and recurrences do not invariably follow heparin reexposure, suggesting the absence of immunologic memory in HIT. 7,8 These observations, in addition to the extraordinary prevalence of PF4/heparin antibody formation in clinical settings such as cardiopulmonary bypass, 9 cast doubt on the requirement for T-cell help in the generation of anti-PF4/heparin antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…DPT is sometimes termed controlled challenge or reexposure (1), drug challenge (2), graded (2) or incremental challenge (3), test dosing (2), rechallenge (4), or testing for tolerance (5). DPT is recommended by some specialized centers (6–9), allergy societies (2), and text books (6, 10), whereas other societies advise against performing DPTs (11), and some review articles (12) and textbooks (13) do not even mention the method. The topic DPT is controversial in general and the test procedures not validated in most instances.…”
mentioning
confidence: 99%
“…In fact, ADRs are results of complex reactions of drugs with biological components. Some studies have shown that drug side effects can be the results of reactions of drug chemicals with proteins [5,6,36], which interrupts normal biological processes leading to abnormal reactions of human bodies. By using this kind of data, we can improve the performance of models and extract possibly associated biological components with ADRs.…”
Section: Non-clinical Datamentioning
confidence: 99%